Tuning the ionic conductivity of flexible polyvinyl alcohol/sodium bromide polymer electrolyte films by incorporating silver nanoparticles for energy storage device applications. Issue 28 (6th May 2022) - Cyriac, Vipin; Molakalu Padre, Shilpa; Ismayil,; Sangam Chandrashekar, Gurumurthy; Chavan, Chetan; Fakeerappa Bhajantri, Rajashekhar; Murari, Mudiyaru Subrahmanya
Abstract: In this present work, we have synthesized silver nanoparticles (AgNPs) using the chemical reduction method and systematically studied the effect of AgNPs of different loading into polyvinyl alcohol/sodium bromide (PVA/NaBr) polymer electrolytes. X‐ray diffraction and Fourier transform infrared spectroscopy confirmed the variation in the crystallinity and complexation with AgNPs loading, respectively. AgNPs are uniformly distributed in the polymer matrix as depicted in FESEM. According to transport property studies, it is observed that carrier concentration has a strong influence on ionic conductivity. Additionally, I‐t studies showed that most charge carriers are ions and not electrons. The sample PVA/NaBr with AgNPs, prepared from 6 mM AgNO3 solution (PNAg6) with ionic conductivity 1.22 × 10 −4 S cm −1 (one order increase with respect to undoped sample) and highest electrochemical stability window (ESW) of 2.86 V, can be chosen as a suitable candidate for energy storage device applications. Abstract : Graphical abstract created with biorender.com